Short communication: Paracheck-Pf®: A new, inexpensive and reliable rapid test for P. falciparum malaria - Proux, S; Hkirijareon, L; Ngamngonkiri, C; McConnell, S; Nosten, F (2001)
We compared the performance of Paracheck-Pf®, a new and cheap rapid malaria test, with ICT-Pf/Pv® and microscopy in two malaria surveys in Thai villages on the Thai-Burmese border. The specificity, sensitivity, predictive positive and negative values of the Paracheck-Pf® and ICT-Pf® tests were calculated taking microscopy results as the gold standard. The 294 ICT-Pf/Pv tests resulted in two invalid (no control line) and 11 doubtful results. Both the ICT-Pf/Pv® and Paracheck-Pf® tests reliably detected P. falciparum infections. However, Paracheck-Pf® failed to detect three P. falciparum cases and likewise, ICT-Pf/Pv® failed to detect the same three cases and an additional four cases. These seven cases were detected by microscopy and had a parasitaemia under 150 parasites/μl. At a cost of c. US $1.00, the Paracheck-Pf® test, based on the detection of the P. falciparum specific HRP-2 protein, is a reliable, easy to use and affordable tool for the diagnosis of P. falciparum malaria.